Auswirkungen von Weinbergsflurbereinigungen auf die Sozial- und Wirtschaftsstruktur der Weinbaubetriebe - am Beispiel der Verfahren Boppard I und Oberwesel I, Oberes Mittelrheingebiet - Hahn, Helmut (ERDKUNDE, 1977)
Beyond technical measures, such as the consolidation of parcels of land, road building etc., Flurbereinigung is intended to contribute to the improvement of farm-size structure in the consolidation areas. The consolidation projects of Boppard I and Oberwesel I are taken as case studies to examine, on the basis of a questionnaire at all the holdings affected, whether this second and essentially long-term aim has met with success. The investigation shows that although Boppard, with a relationship of 28 sufficiently large full-time holdings (averaging 2.5 ha) to 31 part-time holdings (averaging 0.4 ha) experienced a structural improvement, Oberwesel with 18 full-time holdings (averaging 3.0 ha) to 46 over-large part-time holdings (averaging 0.6 ha) did not. In Boppard the change in conditions concommitant with the size of holding, with all that follows from it, such as mechanical equipment, choice of grape variety etc., is the result of the private initiative of young full-time viticulturalists. Beyond this, however, the investigation makes it clear that nothing but individual advice at the right time and by neutral institutions can lead to improvement in the structure of holdings and thus to the preservation of the landscape of vine growing as a tourist attraction.